Exploring The Potential Of The Marketplace: Benefits And Challenges For Online Sellers - Fitri Wahyuni; Mhd.Sahrizal; Siti Saidah; Evan Marsandi; Titin Sumarni (Interkoneksi: Journal of Computer Science and Digital Business, 2024)
The shift in people's shopping styles is also marked by the growth of available e-commerce marketplaces. This is an opportunity for small businesses to be involved in the growing choice of e-commerce marketplaces that can be accessed for free. According to the goukm.id site, the involvement of small businesses in the online market can increase economic growth in Indonesia. Marketplace is a platform where producers and consumers can meet to carry out buying and selling transactions for products or services using shopping applications or websites. In this platform, buyers can explore various products or services offered by various manufacturers from different online stores. The existence of a halal marketplace is closely related to the support provided by the government, especially from the National Sharia Finance Committee, one of which includes the 2020-2023 Indonesian Sharia Economic Masterplan program which seeks to contribute to the growth of a digital economy that follows sharia principles through the development of a halal platform.